A Critique of Positivism: Human Nature and Anarchy - Lama, Sunny (Unity Journal, 2024)
Positivism and post positivism are two paradigms within the field of international relations (IR) that differ in their approaches to ontology (the nature of reality) and epistemology (how knowledge is acquired) in the study of international politics. Ontologically, positivists are objectivists, meaning that they believe there are objective facts (for example, selfish human nature) and laws (for example, anarchy leads to chaos) in international politics. Positivists apply common rationality and value-neutrality as epistemological tools to discover and analyze such claims regarding external and objective social reality. In this paper, I make two points. First, positivism (realism and liberalism) has a natural propensity to reify social concepts into trans historical essence to generate causal theories. However, in reality, human nature is complex and the meaning of social realities such as human nature and anarchy is conceptual and constitutive. Second, the adoption of common rationality and value-neutrality as epistemological building blocks lead positivism to a rigid and ahistorical view of human nature and anarchy. In contrast, post positivism (critical theory and constructivism) can generate a relatively nuanced and complete picture of international politics.